Measurement, analysis and prediction of amoxicillin oral dose stability from integrated molecular description approach and accelerated predictive stability (APS) - Merienne Camille; Marchand Chloe; Filali Samira; Salmon Damien; Pivot Christine; Pirot Fabrice (De Gruyter, 2020)
Stability of low amoxicillin oral dosage form (5 mg) used in reintroduction drug test was not fully documented. Furthermore, the impact of (1) salt moiety of amoxicillin and (2) amoxicillin - excipient interactions upon the antibiotic formulation stability during the storage was not characterized so that the estimation of the pharmaceutical expiration date from shelf-life was uncertain. Thus, the main goal of this study was to estimate the shelf-life of two formulations of amoxicillin, using a semi-predictive methodology.